Analisis Trend Laporan Keuangan untuk Menilai Kinerja Keuangan PERUMDA Air Minum Tirto Negoro Kabupaten Sragen Periode Tahun 2021-2023 - Hisnati, Nafia Nur; Kusumastuti, Anggit Diah; Mutiasari, Annisa Indah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study was conducted with the aim of analyzing trends in the financial statements of PERUMDA Air Minum Tirto Negoro Sragen Regency during the 2021-2023 period to assess the company's financial performance. The method used is trend analysis with a focus on changes in key accounts such as assets, liabilities, equity, and receivables. This research is descriptive quantitative using secondary data in the form of annual financial statements. The results of the analysis show that there is a significant increase in fixed assets, which reflects the existence of long-term investments to support the smooth operation and expansion of the company. The decrease in liabilities indicates that the company is successful in managing debt more efficiently, which contributes to the improvement of liquidity conditions. In addition, the increase in equity driven by a grant from PT Oasen Netherlands further strengthened the company's capital structure and competitiveness in the water supply industry. Overall, PERUMDA's financial performance experienced consistent improvement over the analyzed period. This indicates that good financial management can support the company's operational sustainability and future growth and reflects efficiency in the management of the company's assets and liabilities.